Review Of Cryptocurrency Based On Sharia Economic Law - Agung Subayu Koni (Faculty of Law, Universitas Pekalongan, 2023)
cryptocurrencies still often clash with applicable law, not least with sharia economic law because Indonesia has a majority Muslim population, so sharia review in the use of cryptocurrencies is essential, so in this case, the Indonesian Ulema Council issued an unlawful fatwa regarding the use of cryptocurrencies both as currency. or as a digital asset. This study aims to analyze and explain cryptocurrencies based on the provisions of Islamic economic law in their use in money or as digital assets, using normative juridical research methods. The results of this study found that the use of cryptocurrencies has two functions, namely as currency and digital investments, but the use of cryptocurrencies clashes with the concept of Islamic economics because cryptocurrency has elements of dharar, ghrara, and qimar, also the idea of money in cryptocurrency clashes with the concept of money in Islam.